IMPLEMENTASI INTEGRASI PEMBELAJARAN AL-QUR’AN DAN BAHASA ARAB DALAM MENINGKATKAN KEMAMPUAN MEMBACA TEKS ARAB SANTRI DI RUMAH ILMU AL-QUR’AN (RIQA) - Aris Liswanto (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
This study is motivated by the low ability of some students (santri) in reading Arabic texts, particularly in terms of pronunciation accuracy (makhraj), reading fluency, and vocabulary comprehension. In practice, the teaching of the Qur’an and Arabic language has often been conducted separately, resulting in less optimal outcomes in developing students’ Arabic reading skills. This study aims to describe the implementation of an integrated learning model combining Qur’anic instruction and Arabic language learning, as well as its impact on students’ ability to read Arabic texts at Rumah Ilmu Al-Qur’an (RIQA). This research employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving 15 students. The findings indicate that the integrated learning model significantly improves students’ ability to read Arabic texts, as evidenced by improvements in pronunciation accuracy, reading fluency, and vocabulary comprehension. The integration model is implemented through the Jibril method (talqin–talaqqi), repetition (takrir), and habituation (ta’wid) in a systematic manner. Supporting factors include a Qur’anic learning environment and structured instructional methods, while inhibiting factors include differences in students’ initial abilities and limited instructional time. This study recommends the integrative learning model as an effective approach to Arabic language instruction based on the Qur’an, particularly in enhancing students’ reading competence in a more contextual and meaningful way.